2015
DOI: 10.1038/jhg.2015.116
|View full text |Cite
|
Sign up to set email alerts
|

BMPER variants associated with a novel, attenuated subtype of diaphanospondylodysostosis

Abstract: Diaphanospondylodysostosis (DSD), caused by loss of bone morphogenetic protein-binding endothelial regulator (BMPER), has been considered a lethal skeletal dysplasia characterized by severe deficiency of vertebral body and sacral ossification, reduced rib number and cystic kidneys. In this study, however, we have demonstrated that variants in BMPER may cause a milder disorder, without renal anomalies, that is compatible with long-term survival. Four siblings, three males and one female, presented with severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Previous reports ascertained biallelic BMPER mutations in six patients with DSD [ 9 , 13 ] and three siblings with attenuated DSD [ 12 ]. In this report we show that ISD a disorder phenotypically similar, but much milder, than DSD is also caused by biallelic mutations in the BMPER gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports ascertained biallelic BMPER mutations in six patients with DSD [ 9 , 13 ] and three siblings with attenuated DSD [ 12 ]. In this report we show that ISD a disorder phenotypically similar, but much milder, than DSD is also caused by biallelic mutations in the BMPER gene.…”
Section: Discussionmentioning
confidence: 99%
“…Parental consanguinity in one patient suggested autosomal recessive inheritance, but the causative gene has been hitherto unknown [ 2 ]. Diaphanospondylodysostosis (DSD) is a lethal/semilethal skeletal dysplasia, the phenotype of which is similar to, but more severe than, that of ISD [ 5 12 ] (Additional file 1 : Tables S1 and Additional file 2 : Table S2). Funari et al identified mutations in the BMPER in four patients with DSD [ 13 ], and since then two additional DSD patients and three siblings with so-called attenuated form of DSD with BMPER mutations have been published [ 9 , 12 ] (Table 1 , Fig.…”
mentioning
confidence: 99%
“…Cross talk with various BMP modulators, ECM components, and cell-surface proteins may thus provide a basis for the activities of Cv2/Bmper as agonist or antagonist of BMP ligands. Mutations in BMPER have been linked to an autosomal recessive perinatal lethal skeletal disorder, diaphanospondylodysostosis, in humans (Funari et al 2010;Ben-Neriah et al 2011;Zong et al 2015).…”
Section: Crossveinless-2 (Bmper/cv-2)mentioning
confidence: 99%
“…Biallelic pathogenic variants in BMPER are also known to cause diaphanospondylodysostosis (DSD) (OMIM #608022), a perinatally lethal condition (Funari et al ). Attenuated DSD with features overlapping with ISD and DSD has been reported in a family with biallelic variants in BMPER (Zong et al ). All the three conditions have overlapping features and demonstrate the spectrum of severity of the BMPER related conditions.…”
mentioning
confidence: 95%